Analisis Framing Model Robert N. Entman pada Kasus Korupsi Pertamina: Studi pada Kompas.com dan Tempo.co - Lasria Sinambela (Law and Communication Journal, 2025)
Abstract In Indonesia, corruption is still a media concern, especially with regard to large companies such as Pertamina. The purpose of this research is to see how the news about Pertamina's corruption case was broadcasted in the online media Kompas.com and Tempo.co, using Robert N. Entman's framing model. Framing analysis was used as a qualitative descriptive method to determine how the two media framed the information. The study showed that Kompas.com and Tempo.co used different methods to define the problem, identify its causes, provide moral judgment, and provide solutions. Tempo.co concentrates on the parties involved and the legal process, while Kompas.com concentrates on the impact of corruption on the economy and society. This study found that the media, through framing the news and acting as a watchdog for the government and related institutions, plays an important role in shaping public opinion. Keywords: Framing, Pertamina, Corruption, Kompas.com, Tempo.co